GROUNDWATER STRESS ASSESSMENT IN THE PIRACICABA, CAPIVARI AND JUNDIAÍ RIVER BASINS (PCJ). - de Paula E Silva, Flavio; Fischer, Tiago Vier; Ezaki, Sibele; Gastmans, Didier [UNESP]; Rodrigues, Vinícius Rosa; Albuquerque Filho, José Luiz; Franzini, Andrea Segura; Noale, Julia Octaviano (Derbyana, 2021)
This article presents the results of an assessment of groundwater stress in the aquifers present in the Piracicaba, Capivari and Jundiaí river Basins, located in southeastern Brazil, with over 15,378 km2, 92.5% of which belongs to the State of São Paulo and a small part (7.5%) to the State of Minas Gerais. The assessment of water stress in aquifers is based on consumption and availability indicators. The consumption indicator used was the exploitation density, calculated using the Kernel Density geoprocessing tool, using the flow data from 11,621 wells obtained from the Department of Water and Electric Energy - DAEE, complemented with data from Minas Gerais State, extracted from the CPRM - Geological Survey of Brazil database. The availability indicator used the Q95 minimum flow rate, calculated from the hydrological regionalization studies carried out by DAEE. Applying the geoprocessing method of subtracting the grids from the water availability and exploitation intensity maps, the water stress map was obtained, expressed in terms of water balance. The stress map discriminates areas with water deficit (negative balance) from areas with water overplus (positive balance), in terms of available annual flow rate (m3/year). The method proved to be efficient in the identification of areas with water deficit, making it possible to direct management efforts to monitor and apply usage and protection guidelines.
AVALIAÇÃO DO ESTRESSE HÍDRICO SUBTERRÂNEO DAS BACIAS HIDROGRÁFICAS DOS RIOS PIRACICABA, CAPIVARI E JUNDIAÍ (PCJ)
Keywords: Hydrogeology; Management; PCJ Basins; Water stress